Differences in the Management of Pediatric Facial Trauma - Braun, Tara L.; Xue, Amy S.; Maricevich, Renata S. (Seminars in Plastic Surgery, 2017)
Craniofacial trauma is common in the pediatric population, with most cases limited to soft tissue and dentoalveolar injury. Although facial fractures are relatively rare in children compared with adults, they are often associated with severe injury and cause significant morbidity and disability. Initial evaluation of a child with facial trauma generally involves stabilizing the patient and identifying any severe concomitant injuries before diagnosing and managing facial injuries. The management of pediatric facial fractures is relatively more conservative than that of adults, and nonsurgical management is preferred when possible to prevent the disruption of future growth and development. Outcomes depend on the site of the injury, management plan, and subsequent growth, so children must be followed longitudinally for monitoring and the identification of any complications.
Keywords: pediatric facial trauma; facial fractures; reconstructive surgery